Penggunaan Teknologi Pemerah Otomatis pada Peternakan Sapi Perah dan Dampaknya Terhadap Produktivitas Susu di Desa Bedrug - Dyah Rahmatika Anjani; Teguh Ansori (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This article examines the implementation of automatic milking technology in dairy farms and its impact on milk productivity in Bedrug Village. The aim of this study is to evaluate the efficiency and benefits of automatic milking technology in increasing milk production in dairy farms. A field survey method was used to collect data from several dairy farms that have adopted automatic milking technology in Bedrug Village. The collected data included a comparison of milk productivity before and after the implementation of the technology, as well as the farmers' responses to using this technology. The results of the study show that the use of automatic milking technology has a positive impact on milk productivity in Bedrug Village. The implementation of this technology improves the efficiency of the milking process, resulting in increased milk production. Moreover, the technology also helps reduce stress on dairy cows and improves animal welfare. Thus, this article presents evidence that the use of automatic milking technology can be an effective solution to enhance productivity and animal welfare in dairy farms, ultimately contributing to the development of the dairy industry in Bedrug Village.